Survey on digital dependency, writing by hand, and group learning as learning styles among Japanese medical students: Assessing correlations between various accomplishments - Nobuyasu Komasawa; Kimitaka Takitani; Sang-Woong Lee; Fumio Terasaki; Takashi Nakano (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Although digital learning devices have become increasingly more common in medical education settings, it remains unclear how they influence medical student learning styles and various outcome measures. This study aimed to assess student learning styles, specifically as they relate to digital dependency, writing habits, and group learning practices among current medical students. MATERIALS AND METHODS: This questionnaire study was approved by the Research Ethics Committee of Osaka Medical and Pharmaceutical University. We conducted a questionnaire survey of 109 medical students who were 5th year students during the 2021 school year. Medical students were asked about their level of digital dependency, writing by hand, and group learning practices. We also analyzed the correlation between student learning styles and their respective outcomes on several summative evaluations. RESULTS: Of the 109 students targeted, we received responses from 62 (response rate, 56.8%). Among the respondents, digital dependency was 83.4 ± 18.6%, while hand writing ratio 39.8 ± 29.9% and group learning ratio 33.5 ± 30.5%. We also assessed correlations between these learning styles and scores on the CBT, OSCE, CC, and CC Integrative Test. Only writing by hand showed a small positive correlation with CC Integrative Test scores. CONCLUSION: Our questionnaire survey assessed the rates of digital dependency, writing by hand, and group learning practices, and analyzed the correlations between these learning styles and respective outcomes. Current medical students exhibited high digital dependency which was not correlated with performance outcomes.